IMPLEMENTASI METODE AGILE DEVELOPMENT DALAM PERANCANGAN SISTEM INFORMASI PEMESANAN MENU PADA RESTORAN - M.Kom, Walim; Pohan, Achmad Baroqah; Safrudin, Azman (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2022)
The development of businesses carried out by business people is not far from the development of internet technology to make these businesses superior and ready to compete in this era. The number of competitors makes business people have to innovate in creating ideas to be able to attract customers and make them more effective and efficient in running their business as well as in the restaurant business. Sentral Aljazeerah Epicentrum is a restaurant that serves Middle Eastern-style food or dishes located in Kuningan. Based on research on qraved, it shows that typical middle eastern restaurants in Jakarta have at least more than 40 restaurants, and to compete among these restaurants, they must have an effective and efficient ordering system. At the Aljazeerah Epicentrum restaurant, in carrying out services to customers to place orders, they still use book notes or just written on paper, so that the service becomes ineffective and seems long if the restaurant is receiving many visitors and an error is found in recording orders, not to mention if the customer asks for an explanation. about the menu you want to order. For that we need a system that helps the problems that have been described above, namely creating a web-based ordering system using an intranet network, in making the system, the software development process uses the agile method, where the agile method helps facilitate the process of developing information systems because the agile method prioritizes user satisfaction.